Effects of atorvastatin on atrial remodeling in a rabbit model of atrial fibrillation produced by rapid atrial pacing. Issue 1 (December 2016) - Yang, Qian; Qi, Xiaoyong; Dang, Yi; Li, Yingxiao; Song, Xuelian; Hao, Xiao
Abstract Background Accumulating evidence suggests that myeloperoxidase (MPO) is involved in atrial remodeling of atrial fibrillation (AF). Statins could reduce the MPO levels in patients with cardiovascular diseases. This study evaluated the effects of atorvastatin on MPO level and atrial remodeling in a rabbit model of pacing-induced AF. Methods Eighteen rabbits were randomly divided into sham, control and atorvastatin groups. Rabbits in the control and atorvastatin groups were subjected to rapid atrial pacing (RAP) at 600 bpm for 3 weeks, and treated with placebo or atorvastatin (2.5 mg/kg/d), respectively. Rabbits in the sham group did not receive RAP. After 3 weeks of pacing, atrial structural and functional changes were assessed by echocardiography, atrial effective refractory period (AERP) and AF inducibility were measured by atrial electrophysiological examination, and histological changes were evaluated by Masson trichrome-staining. The L-type calcium channel α1c (Cav1.2), collagen I and III, MPO, matrix metalloproteinase (MMP)-2 and MMP-9 were analyzed by real time polymerase chain reaction and/or western blot. Results All rabbits were found to have maintained sinus rhythm after 3 weeks of RAP. Atrial burst stimulation induced sustained AF (>30 min) in 5, 4, and no rabbits in the control, atorvastatin, and sham groups, respectively. The AERP shortened and Cav1.2 mRNA level decreased in the control group, but these changes were suppressed in the atorvastatin group. Obvious left atrial enlargement and dysfunction was found in both control and atorvastatin groups. Compared with the control group, these echocardiograhic indices of left atrium did not differ in the atorvastatin group. Prominent atrial fibrosis and increased levels of collagen I and III were observed in the control group but not in the atorvastatin group. The mRNA and protein levels of MPO, MMP-2 and MMP-9 significantly increased in the control group, but these changes were prevented in the atorvastatin group. Conclusion Treatment with atorvastatin prevented atrial remodeling in a rabbit model of RAP-induced AF. The reduction of levels of atrial MPO, MMP-2 and MMP-9 may contribute to the prevention of atorvastatin on atrial remodeling.